Research on current assisted flexible mold micro-forming process based on single channel - Qingjuan Zhao; Gui Wang; Jinchao Sun; Ruoyu Zhang; Lejia Zhou; Yunfei Qu (Materials Research Express, 2025)
Aiming at the problems such as poor forming accuracy and serious thickness thinning in sheet metal bulging, a method of current-assisted flexible mold forming was proposed. The single channel flexible mold forming experiment was carried out with 304 stainless steel sheet as the experimental material. Firstly, the microstructure change of the sheet under the action of current was analyzed. Then, the flexible mold bulging law of stainless steel sheet was explored from two aspects of current intensity and pressure holding time. Finally, the difference between the traditional rigid mold and the flexible mold is compared. The experimental results show that with the increase of the pretreatment current, the fibrous distribution in the thickness direction of the sheet is alleviated, the work hardening is weakened, the bulging depth of the flexible mold is gradually increased, and the wall thickness distribution is more uniform. When the current is 25 A, the bulging depth of the rolled sheet increases from 841 um to 903 um, an increase of about 7.4%. The thinning rate of rounded corners was reduced from the initial 30.05% to 12.74%. When the pressure holding time is increased from 1.5 s to 3.5 s, the wall thickness thinning in each area is improved, and the thinning at the rounded corner is reduced to about 10.66%. Under the same experimental parameters, the bulging of flexible mold is better than that of rigid mold, the single channel profile is clearer, the surface roughness is lower, and the forming performance is better.